The Role of Working Memory in Shaping EFL Learners’ Sentence Complexity - Afzylianur Harahap; Alya Fadhillah Daimunthe; Putri Zahriah; Yani Lubis (International Journal Multidisciplinary Science, 2026)
Sentence complexity is widely regarded as an indicator of second language proficiency, yet many EFL learners struggle to produce structurally complex sentences despite having adequate grammatical knowledge. This study investigates the role of working memory in shaping EFL learners’ sentence complexity from a psycholinguistic perspective. Rather than treating sentence complexity as a purely linguistic outcome, the study examines it as a product of cognitive capacity during language production. Using a qualitative design, the study involved ten undergraduate EFL learners who completed sentence production tasks followed by stimulated recall interviews. The production data were analyzed to identify patterns of sentence complexity, while the interview data were used to explore learners’ cognitive experiences during sentence construction. The findings reveal that working memory strongly constrains learners’ ability to produce complex sentences. When cognitive load increased, learners consistently simplified sentence structure by reducing clause embedding and sentence length. Learners reported difficulty maintaining multiple linguistic elements simultaneously, particularly when lexical retrieval and grammatical organization competed for limited working memory resources. As a result, learners often prioritized meaning clarity and sentence completion over structural complexity. The study also shows that learners were aware of their working memory limitations and consciously adjusted sentence structure to manage cognitive demands. These findings support resource-limited models of language production and highlight working memory as a key factor influencing syntactic performance in EFL contexts. Pedagogically, the study suggests that expectations of sentence complexity should consider cognitive constraints and task conditions. Recognizing the role of working memory can lead to more realistic instruction, better task design, and fairer assessment of learner proficiency.